The Role of the Tax Court as the First and Final Court in Resolving Tax Disputes - Rina Rahmawati Sa’adah; Nida Muron Heriandini; Hanifah Purnamasari; Rini Irianti Sundary (Fox Justi : Jurnal Ilmu Hukum, 2025)
Tax is an obligatory contribution to the state payable by individuals or bodies without direct compensation for state purposes to benefit the people. The tax dispute between PT Prima Globalindo Logistik, Tbk. and the Director General of Taxes on Tax Underpayment Assessment Letter Number 00176/6/207/19/048/21 shows how illegal tax collection can unfairly tax taxpayers. This study examines how people settle tax disputes over Directorate General of Taxes underpayment tax assessment letters through the tax court. As well as other goals to guide Tax Court judges' tax dispute decisions. This study applied normative juridical data collection methods to literature studies and secondary data. This study shows that taxpayers contest the Tax Underpayment Assessment Letter Number 00176/6/207/19/048/19 in two stages: objection efforts at the Tax Determination Office. Taxpayers seek an appeal if they haven't found a remedy. In the appeal, the tax court partially upheld the Director General of Taxes' decision on the taxpayer's challenge to Tax Underpayment Assessment Letter Number 00176/207/19/048/21.